The Analisis Keterampilan Komunikasi Ilmiah Siswa SMA melalui Pembelajaran Project Based Learning pada Materi Energi Alternatif - Afkarina, Dina; Aminuddin, Helmi; Lesmono, Albertus Djoko; Nuraini, Lailatul (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2024)
Scientific communication skills are included in the 21st century skills, where this skill refers to an individual's ability to communicate clearly in orally and writing. To determine student’s scientific communication skills, we needed applied learning activities who support this skill and one of them is Project Based Learning learning model. Project based learning is a learning strategy that empowers students to gain new knowledge and understanding. The aim of this research is to analyze scientific communication skills for senior high school students' on alternative energy material. This research is a quantitative descriptive research with a case method design. This research was placed at SMAN 1 Jember in the odd semester of the 2023/2024 academic year. The data collection method used is through tests, observation and documentation. Research data were analyzed using descriptive statistics.The result of this research is known that students' scientific communication skills are included in the quite good category. The best indicator of scientific communication skills is the use of scientific language terms with an achievement of 80%, while the indicators of composing scientific topics, conveying natural phenomena specifically and representing findings or evidence have an achievement of 60%. When observations were made, students had carried out their roles well. Teachers guide and motivate students and students are active and enthusiastic when learning takes place.